Keabsahan Wakaf Intellectual Property Right dalam Undang-Undang Perwakafan di Indonesia Menurut Hukum Islam - Moch Nurcholis (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
The discourse about waqf property in Islamic Law is closely related to the formulation of the concept of property. The discourse revolves around the question of whether the definition of the waqf object refers to its material side in the sense of ‘ainul al-waqf, or does it refer to the substance side in terms of benefits and results. Can immaterial objects such as Intellectual Property Right can be used as endowments. This research is a type of qualitative research. Judging from the data collection type library research. The approach used is juridical-normative. In data analysis, the author uses content analyst methods, descriptive using a deductive mindset. The results of the study concluded that the waqf in the form of Intellectual Property Right as contained in the Indonesian Representative Law in Indonesia is valid according to Islamic Law, because it has been in accordance with the view of one of the schools of fiqh, namely the mâlikîy school, which permits waqf in the form of benefits. This conformity is produced through the method of ilh{âq al-masâ?il bi nad{âirihâ (equating a problem with a comparable one). The point of conformity between the two is equally including objects that are immaterial